2016
DOI: 10.18805/ijar.10975
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different diagnostic test to detect feline panleukopenia virus among cats in Kerala, India

Abstract: Feline panleukopenia (FPL) is an acute viral infection of domestic and wild felids causing high mortality among non immune kittens. Commercially available immunochromatographic (IC) strips, haemagglutination (HA) test and polymerase chain reaction (PCR) were employed to detect FPLV. In the current study IC strip test and HA test were compared with PCR. A total of 27 faecal samples from cats clinically suspected for FPL infection were collected from five districts of Kerala, India. Out of 27 samples tested, 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Early and timely diagnosis is imperative for effective disease management and containment, vital in halting the dissemination of FPLV. Raheena et al (2017) found that, PCR is a sensitive, specific and rapid technique for FPV detection, while sensitivity of LFA is poor.…”
Section: Treatment and Discussionmentioning
confidence: 98%
“…Early and timely diagnosis is imperative for effective disease management and containment, vital in halting the dissemination of FPLV. Raheena et al (2017) found that, PCR is a sensitive, specific and rapid technique for FPV detection, while sensitivity of LFA is poor.…”
Section: Treatment and Discussionmentioning
confidence: 98%
“…The virus isolation can be used for diagnostic purposes. However, it requires enormous effort, time, and specialized personnel, and additional tests such as immunofluorescence and hemagglutination must be performed to detect the viral antigens (Raheena et al 2017). Due to its high sensitivity and specificity, the PCR technique is widely applied to diagnose several diseases (Chowdhury et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…These finding disagreements with Awad et al [16] they mentioned that the sensitivity, specificity and accuracy of ELISA were 88%, 100%, and 94.5% respectively. Raheena et al [48] stated that polymerase chain reaction (PCR) assay is considered as a highly sensitive, specific and rapid technique for confirmative diagnosis of feline panleukopenia virus (FPV) infection in cats.…”
Section: Discussionmentioning
confidence: 99%